Schopenhauer's politics - Norberg, Jakob, 1975- (Modern European philosophy., 2024)
Arthur Schopenhauer (1788-1860) lived through an era of great political turmoil, but previous assessments of his political thought have portrayed him as a pessimistic observer with no constructive solutions to offer. By assembling and contextualizing Schopenhauer's dispersed comments on political matters, this book reveals that he developed a distinct conception of politics. In opposition to rising ideological movements such as nationalism or socialism, Schopenhauer denied that politics can ever bring about universal emancipation or fraternal unity. Instead, he viewed politics as a tool for mitigating rather than resolving the conflicts of a fundamentally imperfect world. Jakob Norberg's fascinating book reconstructs Schopenhauer's political ideas and shows how they relate to the dominant debates and trends during the period in which he lived. This title is also available as Open Access on Cambridge Core.